Low-carbon tourism of small islands responding to climate change. Issue 3 (3rd July 2018) - Lee, Su-Hsin; Wu, Shih-Chieh; Li, Anna
ABSTRACT: Island has been one of the most attractive tourist destinations in the tourism sector. However, the ecosystems of small islands are particularly vulnerable to climate change. The purpose of this research is to compare the importance and performance of low-carbon tourism in five islands of Taiwan and utilizing the life cycle paradigm as a descriptive comparing discussion to provide suggestions for building resilient and sustainable environment to face climate change impact. There are seven factors in low-carbon tourism policy which are "green energy, green transportation, green building, recycling, green economy, education & partnership, and operator certificate & management". We collected 648 useful questionnaires from Green Island (137), Little Liuqiu (122), Penghu (141), Kinmen (129), and Matsu (119). The results of IPA compared low-carbon policies with evaluation means relatively to suggest suitable strategy for each island. We integrated tourism life cycle to IPA and proposed key aspects of tourism management in development, consolidation, and stagnation stage. In development stage island focuses on green facilities, while for consolidation stage emphasize on the green economy and partnership, and stagnation stage focus on management and resources protection.